PENGARUH MOTIVASI KERJA, KEPUASAN KERJA, DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA (Studi pada Karyawan Kantor Pelayanan Pajak Pratama Semarang Barat) - Burhan Fahrulianzah, 13.05.51.0243 (Students Journal of Economic and Management, 2017)
The purpose this research to analyzes the influence of Work Motivation, Job Satisfaction, Organizational Commitment to Performance. This topic was taken due to the lack of compliance of the number of taxpayers to pay taxes on the Tax Office Pratama West Semarang that indicate the employees performance is still low. This researchâs population are all employee of Tax Services Office Pratama West Semarang who numbered 127 employee. The sampling techniques is using purposive sampling. When collecting data, writers use questionnaire to get information. Data were collected then analyzed by Kaiser Meyer Olkin (KMO) for validity test of the questionâs item, cronbachâs alpha for realibility test, regression test get the result of the effect from each independent variables on dependent variable either partially or simultaneously.The result of this research are : (1) Work Motivation has a positive and significant impact on employee perfomance. (2) Job Satisfaction has a positive but not significant impact on employee perfomance. (3) Organizational Commitment has a positive and significant impact on employee perfomance. Keyword : Work Motivation, Job Satisfaction, Organizational Commitmen, and Perfomance.